AUA guidelines for backfilling and contact grouting of tunnels and shafts - Henn, Raymond W.; American Underground Construction Association (Reston, Virginia London, UK American Society of Civil Engineers Thomas Telford Publications, 2003)
"This book focuses on backfilling and contact grouting performed to fill the voids between the excavated surface and the tunnel and shaft linings, as well as voids between the final structure and the initial support. Although only two types of underground facilities, "tunnels" and "shafts," are used in the title and are referred to throughout, the book is intended to be used in reference to all types of lined underground structures. For example, in addition to transportation, water, and wastewater tunnels, this book can be used for lined underground storage facilities, powerhouses, railroad stations, sports complexes, warehouse and document storage facilities, housing facilities, and other types of lined underground structures."
Keywords: Fills (Earthwork); Grouting; Underground construction; Electronic books